Heterorhabditis bacteriophora Excreted-Secreted Products Enable Infection by Photorhabdus luminescens Through Suppression of the Imd Pathway - Kenney, Eric; Hawdon, John M.; O'Halloran, Damien; Eleftherianos, Ioannis (Frontiers in Immunology, 2019)
Upon entering the hemocoel of its insect host, the entomopathogenic nematode Heterorhabditis bacteriophora releases its symbiotic bacteria Photorhabdus luminescens, which is also a strong insect pathogen. P. luminescens is known to suppress the insect immune response independently following its release, but the nematode appears to enact its own immunosuppressive mechanisms during the earliest phases of an infection. H. bacteriophora was found to produce a unique set of excreted-secreted proteins in response to host hemolymph, and while basal secretions are immunogenic with regard to Diptericin expression through the Imd pathway, host-induced secretions suppress this expression to a level below that of controls in Drosophila melanogaster. This effect is consistent in adults, larvae, and isolated larval fat bodies, and the magnitude of suppression is dose-dependent. By reducing the expression of Diptericin, an antimicrobial peptide active against Gram-negative bacteria, the activated excreted-secreted products enable a more rapid propagation of P. luminescens that corresponds to more rapid host mortality. The identification and isolation of the specific proteins responsible for this suppression represents an exciting field of study with potential for enhancing the biocontrol of insect pests and treatment of diseases associated with excessive inflammation.